Pengaruh Organizational Citizenship Behavior (Ocb) Terhadap Kinerja Dosen Stie Tri Dharma Nusantara Makassar - Hendro, Andi; Anshar, M Chairul (Patria Artha Management Journal, 2020)
This study aims to determine the Effect of Organizational Citizenship Behavior (OCB) on Lecturer Performance STIE Tri Dharma Nusantara Makassar. Sources of data in this study are primary data and secondary data as well as data collection methods by interview and questionnaire. The sample in this study were 52 people with the simple Saturation Sampling method. The data analysis method used is simple linear regression analysis. The results showed that Organizational Citizenship Behavior (OCB) had a significant effect on lecturer performance as indicated by the equation of results Y= 7,162 + 0,814 with a significance value of 0.000 <0.005, so the hypothesis in this study was accepted.Â